Optimisation of parameters suitable for paddy thresher - Siprali, P; Kavitha, R; Surendrakumar, A; Senthilkumar, T; Sivakumar, S D; Thiyagarajan, R; Thambidurai, S (Plant Science Today, 2025)
Post-harvest processing plays a key role in reducing grain losses and improving overall yield in crops, including paddy. Despite many advancements in agricultural mechanisation, the small and marginal farmers face challenges due to the high cost and limited availability of suitable equipment. This study aims to address this gap by comparing the performance of three types of threshing cylinders: spike tooth, wire loop and rasp bar on two paddy varieties, namely CO 54 and CO 55. The comparative analysis will enable the farmers to select the threshing cylinder best suited for their needs, in maximising output and preserving grain quality. The performance was evaluated across different feed rates (70-126 kg h-1) and cylinder speeds (550-950 rpm). The parameters, such as output capacity, threshing efficiency, unthreshed grain loss, broken grain loss and total grain loss were evaluated. Response Surface Methodology (RSM) was used for optimisation. The results showed that feed rate had a stronger effect than cylinder speed on most performance indicators. Among the three, the spike tooth cylinder gave the best results, with a maximum threshing efficiency of 96.81 % and a consistent output of 67.50 kg h-1 at 650 to 750 rpm and 126 kg h-1 feed rate. It also had the lowest unthreshed loss (3.19 %), broken grain loss (1.47 %) and total grain loss (4.66 %) under these levels of feed rate and rpm. The wire loop cylinder matched the output for CO 55 but had higher losses under extreme conditions. The rasp bar showed the least broken grain loss (0.88 %) but higher total grain loss (up to 16.16 %). CO 55 performed better than CO 54 across all measures. ANOVA results confirmed the significance of results for the variables such as feed rate and cylinder speed, with strong model fits (R² > 0.99). The thresher showed optimal results at feed rate of 90 to 105 kg h-1 and cylinder speed of 650-750 rpm. This study provides valuable insights for improving the efficiency and thereby the sustainability of small-scale paddy threshing by offering optimised operating conditions.